Analysis of the Efficiency and Effectiveness of Local Taxes in BAPENDA Sumedang Regency - Ayi Srie Yuniawati (Journal of Business, Accounting and Finance, 2023)
This research aims to understand the efficiency and effectiveness of local taxes in Sumedang regency. Local tax efficiency involves calculating the allocation of tax revenue used to cover the costs of tax collection-related activities. Tax efficiency is related to the magnitude of collection costs in relation to the actual local tax revenue received. On the other hand, local tax effectiveness refers to the ability of the local government to collect local taxes based on the targeted reveneue amount. The research method used in the preparation of this thesis is a combination of quantitative and qualitative research conducted at the revenue agency of Sumedang Regency. Data collection is done through documentation and interviews. The result of this research indicate that the efficiency of local taxes in Sumedang Regency over the las 6 years from 2017 to 2022 falls into the effective category. The effectiveness of local taxes in Sumedang Regency over the last 6 years from 2017 to 2022 falls into the effective category as well, but when viewed from the achievement perspective, there are years that were not met